Activity‐guided isolation of α‐amylase, α‐glucosidase, and pancreatic lipase inhibitory compounds from Rhus coriaria L. Issue 10 (7th September 2020) - Gök, Hasya Nazlı; Deliorman Orhan, Didem; Gürbüz, İlhan and Aslan, Mustafa
Abstract : Abstract: The leaves and fruits of Rhus coriaria are traditionally used in Turkey for the treatment of diabetes. The aim of the present study is to determine α‐amylase, α‐glucosidase, and pancreatic lipase inhibitory activities of R. coriaria leaf and fruit ethanol extracts (80%), and to isolate active compounds against these enzymes. As a result of the activity‐guided isolation, the active compounds were determined as the amentoflavone, agathisflavone, and 1, 2, 3, 4, 6‐penta‐ O ‐galloyl‐β‐glucopyranose. Agathisflavone, amentoflavone, and penta‐ O ‐galloyl‐β‐glucopyranose inhibited α‐glucosidase with 11.4 ± 0.9, 11.3 ± 0.7, and 4.1 ± 0.1 µM IC50 values, respectively. Furthermore, penta‐ O ‐galloyl‐β‐glucopyranose inhibited α‐amylase with 6.32 ± 0.18 µM IC50 . These three compounds also significantly inhibited ( P < 0.05) pancreatic lipase. The results of high‐performance liquid chromatography analysis showed that penta‐ O ‐galloyl‐β‐D‐glycopyranose was one of the main compounds in both fruit and leaf extracts. Therefore, it may be considered that R. coriaria fruit and leaf extracts can be standardized on this substance and used in the development of both medicinal products and functional food for diabetes. Practical Application: Rhus coriaria (Sumac) is one of the plants that is well known and used around the world as a spice. It is also used against diabetes traditionally. The determination of effective compounds can lead to the standardization and development of both medicinal products and functional foods for diabetes. While the fruits of the plant are used as a spice all around the world, the leaves are generally throw away; therefore, the usage of the leaves to the food and medical industry can lead to beneficial effects on the economy.